Direct Cardiac Actions of Sodium-Glucose Cotransporter 2 Inhibition Improve Mitochondrial Function and Attenuate Oxidative Stress in Pressure Overload-Induced Heart Failure - Li, Xuan; Flynn, Elizabeth R.; do Carmo, Jussara M.; Wang, Zhen; da Silva, Alexandre A.; Mouton, Alan J.; Omoto, Ana C. M.; Hall, Michael E.; Hall, John E. (Frontiers in Cardiovascular Medicine, 2022)
Clinical trials showed that sodium-glucose cotransporter 2 (SGLT2) inhibitors, a class of drugs developed for treating diabetes mellitus, improve prognosis of patients with heart failure (HF). However, the mechanisms for cardioprotection by SGLT2 inhibitors are still unclear. Mitochondrial dysfunction and oxidative stress play important roles in progression of HF. This study tested the hypothesis that empagliflozin (EMPA), a highly selective SGLT2 inhibitor, improves mitochondrial function and reduces reactive oxygen species (ROS) while enhancing cardiac performance through direct effects on the heart in a non-diabetic mouse model of HF induced by transverse aortic constriction (TAC). EMPA or vehicle was administered orally for 4 weeks starting 2 weeks post-TAC. EMPA treatment did not alter blood glucose or body weight but significantly attenuated TAC-induced cardiac dysfunction and ventricular remodeling. Impaired mitochondrial oxidative phosphorylation (OXPHOS) in failing hearts was significantly improved by EMPA. EMPA treatment also enhanced mitochondrial biogenesis and restored normal mitochondria morphology. Although TAC increased mitochondrial ROS and decreased endogenous antioxidants, EMPA markedly inhibited cardiac ROS production and upregulated expression of endogenous antioxidants. In addition, EMPA enhanced autophagy and decreased cardiac apoptosis in TAC-induced HF. Importantly, mitochondrial respiration significantly increased in ex vivo cardiac fibers after direct treatment with EMPA. Our results indicate that EMPA has direct effects on the heart, independently of reductions in blood glucose, to enhance mitochondrial function by upregulating mitochondrial biogenesis, enhancing OXPHOS, reducing ROS production, attenuating apoptosis, and increasing autophagy to improve overall cardiac function in a non-diabetic model of pressure overload-induced HF.